Captain Raptor and the space pirates - O'Malley, Kevin, 1961- (Walker & Co. : Distributed to the trade by Holtzbrinck, 2007)
Captain Raptor and the crew of the Megatooth are called back into action to save the planet Jurassica from rogue space pirates.